In vitro regeneration of Passiflora foetida l - Komathi S; G, Rajalakshmi; S, Savetha; MP, Ayyappadas (Journal of Research in Biology, 2011)
Passiflora foetida is an angiosperm plant with high medicinal value and is becoming less in natural communities. It is used as a bacteriocide, antidysentric and antilithic. Aqueous extracts of leaves or whole plants have been used to treat colic, colds, diarrhea, asthma, and sleeping problems. P. foetida has quick and effective action in burn wounds and is recommended by Brazilian Drugs centre as an antirheumatic. The present study report an efficient in vitro regeneration protocol by using leaf, node, internode and shoot tip explants for this species. Explants are surface sterilized and inoculated in to culture medium with different concentration of growth regulators. The shoot tip derived callus effectively (76%) produced shoots in the MS medium containing BAP and NAA at 3.0 and 0.5 mg/l respectively. The nodal and shoot tip segments derived shoots and rooted effectively (70% & 80%) in the basal medium containing the auxin, IBA and IAA alone at 1.0 mg/l respectively. The nodal callus derived in vitro rooted shoots responded well (92%) in the hardening medium